DYNAMICS OF CHANGE OF THE SHOULDER BONE COMPACT IN THE POSTNATAL ONTOGENESIS OF RABBITS OF THE WHITE VELIKAN, GRAY VELIKAN AND FLANDERS BREEDS - X.B.Yunusov; N.B.Dilmurodov; Z.R.Mirzoyev (TADQIQOTLAR, 2025)
Summary. The features of changes in the morphometric indicators of the dorsal and palmar compact substance of the humeral bone in rabbits of the Grey Giant, White Giant, and Flanders breeds in postnatal ontogenesis have been studied. It has been established that the indicators of the thickness of the dorsal and palmar compact substance of the humeral bone have a specific growth dynamics at various physiological stages of postnatal development in rabbits. It was especially noted that the absolute values of the thickness of the dorsal and palmar compact substance of the humeral bone in rabbits of the 1st and 3rd groups were higher from the first day to 21 days of age compared to the 2nd group.